Getting to standard work in health care : using TWI to create a foundation for quality care - Graupp, Patrick; Purrier, Martha (New York : Productivity Press, 2021)
Addressing the challenges involved in achieving standard work in health care, Getting to Standard Work in Health Care, 2nd Edition describes how to incorporate the Training Within Industry (TWI) methods of Job Instruction (JI), Job Relations (JR) and Job Methods (JM) to facilitate performance excellence and boost employee morale in a health care organization. It not only examines the TWI methodologies but also explains how this program is as vital and applicable in today's health care environment as it was when it was developed to train replacements of an industrial workforce off to fight in WWII. Placing this methodology squarely within the health care paradigm, the book uses easy-to-understanding terminology to describe how these methods can make all the difference in the delivery of quality health care. Supplying the foundation for successful Lean practice in health care, it clearly defines the role of standard work and leadership skills in relation to Lean health care. The updated text includes new case studies of current TWI usage in health care that demonstrates how to successfully roll out a sustainable TWI initiative. All new chapters on Job Relations and Job Methods give insight into the full scope of TWI skills development. Including examples of TWI application during the Covid pandemic, the book provides readers with the understanding of how to use these time-tested methodologies to improve training, increase engagement, and deliver continuous improvement in your organization.
Previous edition: 2013.
Section I: Case for Standard Work in Health Care Chapter 1: When Clinical Best Practice Is Not Actual Practice Chapter 2: The Challenge of Designing Standard Work Chapter 3: Hand Hygiene Training Case Study Chapter 4: Need for Good Instruction Skill Section II: Job Instruction Training Chapter 5: Four Steps of Job Instruction Chapter 6: Breaking Down a Job for Training Chapter 7: How to Organize and Plan Training Section III: Job Relations Training Chapter 8: Four Steps of Job Relations Chapter 9: Problem Prevention Using JR's Foundations for Good Relations Section IV: Implementing TWI into the Working Culture Chapter 10: Starting Out Strong with a Pilot Project Chapter 11: Four Steps of Job Methods Improvement Chapter 12: Integrating TWI into the Culture to Sustain Results Conclusion: A Call to Action
OCLC-licensed vendor bibliographic record.
Keywords: Medical care -- Quality control; Health services administration; Employees -- Training of -- Methodology; Total quality management -- Methodology; MEDICAL / Hospital Administration & Care; MEDICAL / Administration; BUSINESS & ECONOMICS / Leadership